Analisis Faktor-faktor yang Mempengaruhi Keputusan Muzaki dalam Membayar Zakat di Laznas Yatim Mandiri Ponorogo - Ihsan, Abdul Mu’iz (Institut Agama Islam Negeri Ponorogo, 2021)
The phenomenon of considering the potential for zakat mal with the amount of zakat paid by the obligatory zakat is a consequence of various factors. The causes of the insignificance of zakat realization with the existing zakat potential, namely: low understanding and awareness of Muslims about the obligation to pay zakat, reluctance to pay zakat to zakat institutions because they prefer to pay zakat directly to those who are entitled, and are reluctant to pay zakat to zakat institutions because they do not experience the pleasure and benefits immediately. This study aims to see what factors and the most dominant factors influence Muzaki's decision to pay zakat at LAZNAS Yatim Mandiri Ponorogo. This type of research is quantitative with a sample of 100 Muzaki from a population of 2,339 Muzaki who pays zakat at LAZNAS Yatim Mandiri Ponorogo, using probability sampling techniques and sampling methods, namely simple random sampling. Data analysis used validity and reliability tests, test tests and tests with factor analysis. The results of this study there are 8 factors that influence Muzaki's decision to pay zakat, namely the factor of religiosity, image of service quality institutions, income, worship, reliability and responsiveness, occupation or position, factors of empathy. The factor that most influenced Muzaki's decision was the religiosity factor which consisted of 6 variables and had the highest Eigen value, namely 4.669